Computed tomogram guided fine needle aspiration for lung masses: Radiologic-cytologic correlation - Pradhan, A; Gurung, G; Thapa, N B; Rijal, K; Karki, D B (Journal of Chitwan Medical College, 2017)
The primary objective was to compare the results of computed tomography (CT) finding with that of cytology. The secondary objective was to evaluate the safety of CT guided transthoracic Fine Needle Aspiration Cytolofy (FNAC) of lung lesions of various sizes and locations. From December 2014 to June 2016, under CT guidance, FNAC of lung lesion was performed on 64 cases attending KIST medical college and Kathmandu imaging diagnostic center. FNAC was performed by using spinal anesthesia needle (22G/23G). Procedures were carried out under CT guidance. Smears were prepared by materials obtained and were fixed in 95% alcohol. Dry as well as wet slides were prepared. The prepared slides were then examined under light microscope by consultant pathologist. Sixty four patients were enrolled in present study. The age of patients ranges from 24 to 87 year with mean age of 55.5 and male to female ratio of 2:1. Radiologically, out of 64 cases, 49 cases were reported as malignant and 15 cases were reported as benign lesion. However, Cytologically, 39 cases were malignant, 22 cases were benign and 3 cases were suspicious for malignancy (no definite diagnosis established). The CT scan showed Sensitivity of 97.4% to identify the malignant mass as compared to cytology findings. the Specificity, Positive and negative predictive value were calculated as 63.6%, 82.6 and 93.3% respectively. CT guided fine needle aspiration cytology (FNAC) is reliable procedure for evaluation of lung lesion. It is simple and safe procedure with high diagnostic accuracy for the diagnosis of Lung cancer. Compared to biopsy, CT guided FNAC shortens the diagnostic interval and helps in differentiating lung malignancy into different cytopathological types which aids in proper management of the malignant lesion.